Circuit-based grounding electrode considering frequency dependence for different input current - Othman, Ruqayyah (Institute of Advanced Engineering and Science, 2020)
This paper presents a simulation work of circuit-based grounding electrode considering frequency dependence of soil parameters for three input currents which are impulse, AC 50 Hz, and DC. The circuit parameters were determined by using Dwight and Sunde equations where a single horizontal grounding electrode was considered. Scott model was used for the frequency dependent model, to determine the frequency dependent soil resistivity and relative permittivity. It is found that the voltage response of the impulse current was highly affected (75.2%) by the frequency compared to the voltage response of AC 50 Hz and DC. The impulse current response also gave the lowest peak in the analysis by the influence of frequency which make it better compared to the two other inputs. Therefore, it can be concluded that the frequency dependent of soil parameters is crucial and need to be considered in the transient analysis for any kind of input current to obtain accurate results.